Melancholia before the twentieth century: fear and sorrow or partial insanity? - Telles-Correia, Diogo; Marques, João Gama (Frontiers in Psychology, 2015)
Throughout the history of Psychopathology, several meanings have been assigned to the term melancholia. The main ones were related to affective (fear and sadness) and thought disorders (a type of mental disorder characterised mainly by the presence of abnormal believes). At the time of Hippocrates melancholia was regarded mainly in its affective component. Since that time, and until the 18th century, authors and opinions have been divided, with both aspects (affective and thought disorders), being valued. Finally, in the 18th-19th centuries, with Pinel at its peak, melancholia becomes exclusively a synonym of thought disorders (abnormal believes: delusions/overvalued ideas). At the turn of the 19th to the 20th century, the affective component returns as the main aspect characterising melancholia.